The Influence of Environmental Knowledge, Green Product Knowledge, Green Word of Mouth, Greenwashing, and Green Confusion as Mediator of Green Purchase Intention - Nita Aulia Eka Putri; Rina Suthia Hayu (UNIVED Press, 2024)
Global warming is a major concern throughout the world. In this context, the role of consumers in preserving the environment is increasingly under the spotlight. Consumer purchasing decisions can have a significant impact on business practices. This research aims to explore the relationship between environmental knowledge, green product knowledge, green word of mouth, and greenwashing practices which often become challenges in the business environment. Apart from that, the research explains the role of green confusion as a mediator of greenwashing on green purchase intention. This research provides insight for business practitioners in their efforts to support consumers in making environmentally friendly purchasing decisions. The research methodology adopted a quantitative survey approach, with a research population of consumers who were aware of single-use gallon products. In this study, 150 samples were used. The analytical tool used in the research is SMART PLS 4. The research results found that environmental knowledge has a positive and significant effect on green purchase intention. Apart from that, green word of mouth also has a positive but not significant effect on green purchase intention. However, the most interesting result is the relationship between greenwashing and green confusion. Greenwashing was found to have a positive and significant effect on green confusion. Interestingly, when greenwashing is mediated by green confusion, the results have a negative but not significant effect on green purchase intention. The limitation of this research is the sample size. In future research, it is hoped that the research subjects and sample size will be expanded so that better results can be obtained.